Tanned gelatin: some biophysical and biochemical properties of a new gel exclusion agent and its application to the chromatography of proteins and viruses - Katz, Woolf (Division of Medical Virology, 2020)
The principal aim of this study was to develop a new bed material suitable for gel exclusion chromatography, which would embrace all the desirable characteristics of available materials used for this purpose and if possible improve on some of them. The two most important limitations of existing gel media concern their exclusion limits and rigidity. Agar and agarose have been found satisfactory for the separation of larger molecules including some viruses, but difficulties may arise at low gel concentrations due to the low mechanical strength of the granules. The dextran and polyacrylamide gels have in general a rigidity equal to that of agar and agarose, but cannot be prepared with such large pore sizes and are therefore limited to the separation of smaller molecules.